High-Precision Nuclear Forces From Chiral EFT: State-of-the-Art, Challenges, and Outlook - Epelbaum, Evgeny; Krebs, Hermann; Reinert, Patrick (Frontiers in Physics, 2020)
We review a new generation of nuclear forces derived in chiral effective field theory using the recently proposed semilocal regularization method. We outline the conceptual foundations of nuclear chiral effective field theory, discuss all steps needed to compute nuclear observables starting from the effective chiral Lagrangian and consider selected applications in the two- and few-nucleon sectors. We highlight key challenges in developing high-precision three-body forces, such as the need to maintain consistency between two- and many-body interactions and constraints placed by the chiral and gauge symmetries after regularization.